Life Events and Coping Strategies Among Young People Who Died by Suicide or Sudden Violent Death - Werbart Törnblom, Annelie; Sorjonen, Kimmo; Runeson, Bo; Rydelius, Per-Anders (Frontiers in Psychiatry, 2021)
Objective: Most empirically anchored psychological models of suicide focus either on the perceived situational stress or on vulnerability factors and coping deficits. The interaction between life stressors and vulnerability factors is less explored. Methods: This case-control study examines interactions between life events and coping strategies in three groups of young people: cases of suicide, cases of other sudden violent death (SVD), and control cases. Results: Four coping strategies, two more adaptive and two more maladaptive, were identified. Distinctive of the suicide and the SVD group was significantly less Planful Problem-Solving, and more Escape-Avoidance and Confrontive Coping than among the controls. Furthermore, Confrontive Coping had significantly higher level in the SVD group than in the suicide group. Between-group differences were partly accounted for differences in negative life events, early and late in life. Both target groups experienced significantly more adverse childhood experiences and recent stressful life events than the controls—the suicide group being more exposed to recent stressful life events even in comparison with the SVD group. This might indicate that adverse childhood experiences are a risk factor for both causes of death, whereas proximal stressful life events are a risk factor for death by suicide to a higher degree than for SVD. Conclusions: Improved understanding of the interplay between life events, both in the far past and present, and coping styles, may facilitate the identification of young people at risk of suicide and violent death.